Analisis Pengaruh Capital Adequacy Ratio, Financing to Deposit Ratio, dan Efisiensi Operasional terhadap Profitabilitas Bank Syariah - Putri, Tiara Adelia; Rahmadani, Widia; Nabila, Salsa (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Operational Efficiency (BOPO) on the profitability of Islamic banks, using a case study of Bank Muamalat Indonesia during the period of 2014–2023. Profitability in this research is measured using Return on Assets (ROA). The research employs a quantitative approach with multiple linear regression analysis. The data used are secondary data obtained from the annual financial reports of Bank Muamalat Indonesia. The results show that CAR and FDR have a positive partial effect on ROA, while BOPO has a significant negative effect on ROA. Simultaneously, the three independent variables have a significant influence on bank profitability. These findings indicate that capital risk management, the effectiveness of intermediation functions, and operational efficiency play crucial roles in enhancing the financial performance of Islamic banks. The implications of this study are expected to provide a comprehensive understanding and practical recommendations for improving the financial performance of Bank Muamalat Indonesia.